Atitudes etnolinguísticas do povo Tapuia do Carretão (GO) - Nazário, Maria de Lurdes (2016)
In this thesis, we aimed to discuss the attitudes of Tapuia people in relation to their so questioned indigenous identity, by having an afro indigenous phenotype and speak the Portuguese language, putting focus into some impacts that we observed in this community arising from the performance of their indigenous teachers in the context of their research and other educational practices during their graduation Course - Intercultural Education in the Takinahakỹ Center for Indigenous Higher Education, at Federal University of Goiás (UFG). At different times with Tapuia indigenous teachers, we heard reports in which the community was in an conflict with their ethnocultural and linguistic situation, with a desire to learn their ancestors language to assert themselves indigenous and many of them felt embarrassed to assert indigenous, questioning themeselves about their Indianness, demonstrating a negative Ethnolinguistics attitude, in our interpretation. On the other hand, in 2012, 2013 and 2014, when we attended Study Steps of Intercultural Education in Terra Indígena Carretão, we realized that, despite the aforementioned questions are still a reality, Tapuia indians have lived another time, defending their indigenous identity openly and the tapuia Portuguese was as their mother tongue (RODRIGUES, 2011), discussing and / or disproving the questions people made them based on the discourse of Indianness and giving evidence that their ethnolinguistic attitudes were under a positive move. We base our argument on theories and epistemologies that were developed in countercurrent rational and liberal thought and in search of a relational thought, contextualizing, liberator, with respect for life and ethnic and cultural diversity. Thus, the Paradigms of Complexity (MORIN, 2003, 2010) and Modernity and Coloniality (QUIJANO, 2005; CASTRO GÓMEZ & Grosfoguel 2007; GARCÉS, 2007; MALDONADO-TORRES, 2008) lay up that counter of hegemonic science practiced for centuries and of the dichotomous social structure naturalized according to the Eurocentric thinking. In order to understand the contributions of an educational project to decolonize humans, we rely on the thought of Paulo Freire (1987, 1997, 2002). We also use the Theory of Bourdieu Practice (1998, [1979] 2013) which helps us to discuss the unification policy, embodied in monolingualism policy in colonial Brazil and the concept of attitude from their understanding of social provisions to act a certain way in a social group. In the first chapter, we present the Tapuia people and their ethnic and linguistic history in the context of different indigenous policies that subordinated and decimated indigenous cultures and languages ​​in the context of Goiás people settlements, constructing a not indian subject, with negative attitudes regarding their identity and their own status in society (REZENDE, oral exposure). Still, in this chapter, we put into focus the historical struggles experienced by Tapuia people in the twentieth century due to the landed interests and also discussed the identity conflict experienced by these people, relating them to their ethnolinguistic attitudes. In the second chapter, at first, we carry on about the political and social context of the twentieth century that favored the emergence of differentiated education for indigenous peoples in Latin America, among them, the Graduation Course - Intercultural Education - at UFG. In the third chapter, we report our field of experience with Tapuia people and present the methodological procedures that were used in the research. In the fourth chapter, we discussed the entry of these teachers in the graduation course, their expectations and perceptions of the actions undertaken in the course, trying to emphasize the meeting of these teachers with a pedagogical proposal of questioning that was possible a space for discussion, of recognition and of appreciation of their indigenous identity differentiated. And finally, we discuss some impacts we realized in Tapuia community arising from the performance of Tapuia teachers in the context of their research and other educational practices during their teacher education. In the last chapter, we proposed an argument on the concept of attitude and presented an interpretation of ethnolinguistic attitudes Tapuia. We seek to understand how the Tapuia have thought, felt and reacted in relation to their identity historically marked by the speech of non Indianness that was made in the context of conflicts of power in terms of landed interests. Our defense is that Tapuia teachers along with their people come becoming aware, in terms of Paulo Freire, their reality of historical oppression, with the appreciation of their distinctive identity, the improvement in their self-esteem and empowerment of their positive Ethnolinguistics atitude. Our defense is that Tapuia teachers along with his people come becoming aware, in terms of Paulo Freire, his reality of historical oppression, with the appreciation of its distinctive identity, the improvement in their self-esteem and empowerment of its positive Ethnolinguistics attitude . We understand that these attitudes are strengthening from one to the other way with their constituent components - new knowledge, beliefs, feelings and other possible reactions, depending on the new social representations that are part of the discussions of Tapuia community.